Childhood trauma, dimensions of psychopathology and the clinical expression of bipolar disorders: A pathway analysis. (December 2017) - ,; ,; ,; Henry, C.; Etain, B.; Leboyer, M.; Laouamri, H.; Souryis, K.; Godin, O.; Raust, A.; Sportiche, S.; Geoffroy, P.A.; et al.
Abstract: Background: This study aims at testing for paths from childhood abuse to clinical indicators of complexity in bipolar disorder (BD), through dimensions of affective dysregulation, impulsivity and hostility. Method: 485 euthymic patients with BD from the FACE-BD cohort were included from 2009 to 2014. We collect clinical indicators of complexity/severity: age and polarity at onset, suicide attempt, rapid cycling and substance misuse. Patients completed questionnaires to assess childhood emotional, sexual and physical abuses, affective lability, affect intensity, impulsivity, motor and attitudinal hostility. Results: The path-analysis demonstrated significant associations between emotional abuse and all the affective/impulsive dimensions (p < 0.001). Sexual abuse was moderately associated with emotion-related dimensions but not with impulsivity nor motor hostility. In turn, affect intensity and attitudinal hostility were associated with high risk for lifetime presence of suicide attempts (p < 0.001), whereas impulsivity was associated with a higher risk of lifetime presence of substance misuse (p < 0.001). No major additional paths were identified when including Emotional and Physical Neglect in the model. Conclusions: This study provides refinement of the links between early adversity, dimensions of psychopathology and the complexity/severity of BD. Mainly, dimensions of affective dysregulation, impulsivity/hostility partially mediate the links between childhood emotional to suicide attempts and substance misuse in BD. Highlights: We modelled the links between childhood trauma and outcomes in bipolar disorders. The path-analysis integrated psychological dimensions as mediators. Emotional abuse increased the levels of affective instability and impulsivity. Affective instability partially mediated the association between trauma and suicidal behaviours. Impulsivity/hostility partially mediated the association between trauma and substance misuse.